Heat shock transcription factor 1 facilitates liver cancer progression by driving super‐enhancer‐mediated transcription of MYCN - Yizhe Liu; Qili Shi; Yue Su; Zhiao Chen; Xianghuo He (Cancer Medicine)
Abstract Background Heat shock transcription factors (HSFs) play crucial roles in the development of malignancies. However, the specific roles of HSFs in hepatocellular carcinoma (HCC) have yet to be fully elucidated.Aims:To explore the involvement of the HSF family, particularly HSF1, in the progression and prognosis of HCC. Materials & Methods We conducted a thorough analysis of HSF expression and copy number variations across various cancer datasets. Specifically focusing on HSF1, we examined its expression levels and prognostic implications in HCC. In vitro and in vivo experiments were carried out to evaluate the impact of HSF1 on liver cancer cell proliferation. Additionally, we utilized CUT&Tag, H3K27 acetylation enrichment, and RNA sequencing (RNA‐seq) to investigate the super‐enhancer (SE) regulatory landscapes of HSF1 in liver cancer cell lines. Results HSF1 expression is elevated in HCC and is linked to poor prognosis in several datasets. HSF1 stimulates liver cancer cell proliferation both in vitro and in vivo, partly through modulation of H3K27ac levels, influencing enhancer distribution. Mechanistically, our findings demonstrate that HSF1 transcriptionally activates MYCN expression by binding to its promoter and SE elements, thereby promoting liver cancer cell proliferation. Moreover, increased MYCN expression was detected in HCC tumors and correlated with unfavorable patient outcomes. Discussion Our study sheds light on previously unexplored aspects of HSF1 biology, identifying it as a transcription factor capable of shaping the epigenetic landscape in the context of HCC. Given HSF1's potential as an epigenetic regulator, targeting the HSF1‐MYCN axis could open up new therapeutic possibilities for HCC treatment. Conclusion The HSF1‐MYCN axis constitutes a transcription‐dependent regulatory mechanism that may function as both a prognostic indicator and a promising therapeutic target in liver cancer. Further exploration of this axis could yield valuable insights into novel treatment strategies for HCC.